(untitled) (Global Journal of Science Frontier Research, 2014)
The potential of microalgae as renewable energy feedstock for biofuel production is well recognized in developing countries and it is a large source of biomass for capturing CO 2 on non-arable lands. In the current studies photobioreactor with 2 L capacity was used and operated with generator exhaust gases for algal CO 2 sequestration. The reactor operated on generator exhaust gases with CO 2 ranges from 500-8000 ppm. As CO 2 concentration increased from 500 to 4000 ppm, there were steady increase in biomass 450 mg/l of dry weight till 2000 ppm, but above 2000 ppm there is decline in growth. The fatty acid profiles were more or less constant at all the CO 2 concentrations and maximum lipid content was 48%. The maximum reduction in CO 2 was 70% at 500 ppm whereas it was 52% at 4000 ppm. When CO 2 concentration increased to 8000 ppm without air, algae could not sustain and showed decline in biomass content. CO 2 fixation from generator gases not only reduces greenhouse gases but also help in getting fatty acid as biofuel.